URGENSI NILAI-NILAI UPACARA ADAT MALABOT TUMBE/TUMPE UNTUK PENGUATAN PENDIDIKAN AGAMA KRISTEN DI KABUPATEN BANGGAI LAUT PROVINSI SULAWESI TENGAH - Desika Sudara; Wolter Weol; Sugijanti Supit (MATA GURU: Jurnal Pendidik dan Tenaga Kependidikan, 2026)
The purpose of this research is to describe and explain the Urgency of the Values of the Malabot Tumbe/Tumpe Traditional Ceremony for Strengthening Christian Religious Education in Banggai Laut Regency, Central Sulawesi Province. This research employs a qualitative method with an ethnographic approach. Data was collected through observation, interviews, and documentation. The implementation of the values of the Malabot Tumbe tradition tends to be normative and informative. Teachers place more emphasis on the knowledge of the tradition rather than touching upon the students' affective and conative aspects. Consequently, the dialogue between faith and culture is not truly felt by the students. The Malabot Tumbe culture has not been fully incorporated into the learning design, focusing only on general aspects, and the contextual values of the local culture are merely an addition (optional) in the teaching and learning process in the classroom